The cat was stolen but given back well-fed : the systems of rank-and-file industrial and local democracy in anarchist areas of Spain 1936 – 1939 - Lehtonen, Veli-Valtteri (2021)
This study examines the general-assemblies and technical-administrative committees in anarchist-controlled areas of Spain during the Spanish Civil War. These assemblies and committees existed in urban industry, agricultural collectives, and local governance. I shall therefore examine the assembly-committee dual-structures in the context of urban and agricultural economy, and in local governance.